Analisis Penetapan Harga Jual Produk Batu Bata Merah Ditinjau dari Etika Bisnis Islam - Asngari, Hisam; Kotimah, Kotimah; Septian, Yongki Adi (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study aims to analyze the determination of the selling price of red brick products from the perspective of Islamic business ethics, with a case study in Tondomulyo Hamlet, Gadungan Village, Kediri Regency, Indonesia. This study is motivated by the practice of determining selling prices that vary between buyers, which is considered to have the potential to violate the principle of justice in business ethics. The method used is descriptive qualitative with a case study approach, and data collection is carried out through observation, interviews, and direct documentation in the field. The results of this study indicate that the determination of the selling price of red bricks is influenced by several factors, including production costs, weather conditions, market demand, and the amount purchased. Although producers set prices based on market mechanisms and mutual agreements, there are still differences in prices between consumers, which are based on their bargaining power. From the perspective of Islamic business ethics, this does not fully reflect the principles of justice ('adl), transparency (al-wuduh), and social responsibility (al-mas'uliyah). However, several producers have shown a commitment to the principle of truth (ash-shidq) and social responsibility, for example, by providing discounts for the construction of Islamic boarding schools.